Enhancing the Performance of Shadow Teachers and ABK Therapists Through Self-Efficacy and Specialized Training Across Multi-Level Inclusive Education: A Sequential Explanatory Mixed-Methods Study: A Study of ASD and ADHD Students from Early Childhood Education through Senior High School - Asrini Mahdia (Asosiasi Dosen Muda Indonesia, 2026)
This study examines the effect of teacher self-efficacy (X1) and specialized training (X2) on employee performance (Y) among shadow teachers and ABK (special-needs) therapists in a multi-level inclusive education institution serving students with Autism Spectrum Disorder (ASD) and Attention Deficit Hyperactivity Disorder (ADHD) from early childhood education (PAUD) through senior high school (SMA), located in Jakarta with two branches in West Java. A sequential explanatory mixed-methods design was employed. In the quantitative phase, a total-sampling survey (n = 21) was analyzed using multiple linear regression (SPSS 26); in the subsequent qualitative phase, semi-structured interviews were conducted with three purposively selected respondents to deepen and contextualize the quantitative findings. Results show that self-efficacy has a significant positive effect on employee performance (t = 2.580; p = 0.019; β = 0.382), specialized training has a significant positive effect (t = 3.904; p = 0.001; β = 0.579), and jointly the two predictors explain 71.9% of the variance in employee performance (F = 23.073; p < 0.001; R² = 0.719). Specialized training emerged as the more dominant predictor. The qualitative interviews corroborated these findings, showing that confidence built through repeated hands-on exposure across educational levels, combined with structured, level-differentiated training, translates into perceived competence and improved job performance. These findings imply the need for structured, cross-level training pathways and deliberate self-efficacy- building mechanisms (mentoring, case debriefing, incremental mastery experiences) to strengthen the performance of inclusive-education professionals.